IMPLEMENTASI GAME PERMAINAN TIMUN EMAS BERBASIS ANDROID - Agung Setiadi (Universitas Teknokrat Indonesia, 2021)
This research was conducted on the basis of helping children to get to know about folklore in Indonesia. In addition, this study was conducted to help children in learning the moral values that exist in folklore. This research was conducted by creating an android-based game application with the theme of Gold Cucumber folklore. Children in Indonesia today have begun to forget the cultures that exist in their own country. One of the causes is the influx of foreign cultures that are becoming increasingly popular and starting to erode the indigenous culture of Indonesia. Therefore, the author created an android-based folklore-themed game application so that children can be interested in one of Indonesia's existing cultures. The app was tested using the black box method and the benefits of the application were studied using questionnaire and interview methods. After the application passed in black box testing, the application was tested and received a positive response from existing questionnaires and interviews. With the results of existing research, it can be concluded that this application can carry out its duties to help children in introducing folklore culture and educating moral values well.